Effect of protective glove use conditions on their resistance to needle puncture. (June 2013) - Nguyen, C T; Dolez, P I; Vu-Khanh, T; Gauvin, C; Lara, J
Abstract : With the growing concern about the risk of needle puncture injuries for many professional groups, a study has been undertaken to investigate the interaction between medical (hypodermic) needles and materials used for protective gloves. This paper looks at the impact of glove use conditions on the resistance of their constitutive materials to needle puncture. Mechanical deformations which may result from hand and finger flexion, for example, were shown to induce a large reduction in the puncture force in the case of elastomers. On the other hand, no significant effect of a support material simulating the hand inside the glove was observed on needle puncture resistance. Finally, a reduction in the needle puncture force was recorded with sheets of neoprene rubber after application of a lubricant. These results demonstrate the large contribution of cutting and friction in the needle puncture process.